The Organelle-Specific Regulations and Epigenetic Regulators in Ferroptosis - Zhang, Yixuan; Li, Mingrui; Guo, Yiming; Liu, Shuang; Tao, Yongguang (Frontiers in Pharmacology, 2022)
Ferroptosisis fairly different from other types of cell-death in biochemical processes, morphological changes and genetics as a special programmed cell-death. Here we summarize the current literatures on ferroptosis, including the cascade reaction of key material metabolism in the process, dysfunction of organelles, the relationship between different organelles and the way positive and negative key regulatory factors to affect ferroptosis in the epigenetic level. Based on material metabolism or epigenetic regulation, it is obviously that the regulatory network of ferroptosis is interrelated and complex.